Public validation and its impact on the initial Affordable Care Act enrollment. Issue 2 (3rd April 2019) - Walker, Doug; Nowlin, Edward L.
Abstract: The 2010 Affordable Care Act (ACA) resulted in the creation of state-based marketplaces (SBMs) and federally facilitated marketplaces (FFMs), and provided financial assistance to a portion of those eligible to enroll. This study looks at how choosing to create a SBM rather than a FFM, and the financial assistance provided to some, influenced enrollments rates as signals of support for the ACA in the eyes of those eligible to enroll. The findings show that the enrollment behavior of those most strongly in support of the ACA legislation was influenced by those external signals of support for the ACA.